Sol-gel auto-combustion synthesis of a novel chitosan/Ho2Ti2O7 nanocomposite and its characterization for photocatalytic degradation of organic pollutant in wastewater under visible illumination. (8th June 2022) - Valian, Movlud; Salavati-Niasari, Masoud; Ganduh, Safaa H.; Abdulsahib, Waleed K.; Mahdi, Makarim A.; Jasim, Layth S.
Abstract: In the last few years, the release of toxic contaminants into the ecosystem has expanded dramatically. Hence, multiple photocatalysts have been improved for the elimination of toxic contamination. The manufacture of photocatalysts based on nanostructures is a promising strategy to improve photocatalytic potential. In this regard, Ho2 Ti2 O7 and chitosan-coated Ho2 Ti2 O7 nanocomposites have been manufactured through a facile auto-combustion and co-precipitation route. Diverse factors, including calcination temperature, type of precursor of titanium, solvent, and types of fuels, can affect the structure, purity, morphology, and particle size of samples. Ho2 Ti2 O7 nanostructures are a good candidate for photocatalytic evolution owing to their adequate bandgap (2.5 eV) in the visible region. This is the first study of the photocatalytic efficacy of Ho2 Ti2 O7 and chitosan-coated Ho2 Ti2 O7 nanocomposites. Their photocatalytic performance was explored over several dyes as pollutants, including malachite green, methyl violet, eriochrome black T, methylene blue, acid red 198, methyl orange, and thymol blue under visible radiation. Besides, diverse parameters, such as Ho2 Ti2 O7 contents, dye levels, were studied on the efficiency of the reaction. The results demonstrated that the maximum efficiency of Ho2 Ti2 O7 and its chitosan-coated was perceived over malachite green with degradation percentages of 95.7 and 79.9%, respectively. Ho2 Ti2 O7 nanostructures were highly stable due to their recyclability test and kept their photocatalytic potential over five cycles. The decrease in photocatalytic efficiency in the 5th period is 7.1%. Graphical abstract: Image 1 Highlights: Preparation of Ho2 Ti2 O7 nanostructures and chitosan-coated Ho2 Ti2 O7 nanocomposites by a simple method. Investigation of the effect of different parameters on morphology, purity, and particle size of products. The Ho2 Ti2 O7 nanostructures could efficiently degrade several organic dyes under visible light. The maximum degradation percentage was observed in the presence of malachite green (95.7%). A possible photocatalytic mechanism on Ho2 Ti2 O7 nanostructures was suggested.